Symbolism in the Ngumbuq Tradition in Marong Village, Central Lombok - Baiq Annisa Nanda Arfina (Tabéq Care Center and UIN Mataram, 2025)
The Ngumbuq tradition in Marong Village, East Praya District, Central Lombok Regency, is part of the cultural heritage that is still preserved today. This tradition is rich in deep symbolism, reflected in various elements, including actions, objects, and words, that accompany the procession. This study aims to uncover the symbolic meaning contained in the Ngumbuq tradition and to understand the underlying social, cultural, and religious values. The approach used in this study is qualitative, employing ethnographic methods through participatory observation, in-depth interviews with traditional leaders, religious figures, and community members involved in the tradition, as well as documentation of the procession. The findings reveal that every element in the Ngumbuq tradition carries a specific symbolic meaning. For example, the materials used in the procession symbolise purity, prayer, and hope. The procession reflects togetherness, solidarity, and respect for ancestors. In addition, the verbal expressions that accompany this tradition convey moral advice and religious values. This symbolic meaning not only serves as the cultural identity of the Marong Village community but also as a means of instilling life values, such as cooperation, gratitude, and strengthening social bonds. The Ngumbuq tradition is an example of local wisdom that successfully combines traditional elements and Islamic teachings in a harmonious manner, making it relevant in modern society. This study is expected to contribute to the preservation of local culture and serve as a reference for symbolic anthropology studies, particularly in the context of Lombok culture.